Community Engagement in the Management of Urban Green Spaces: Prospects from a Case Study in an Emerging Economy - Adriano Bressane; Anna Isabel Silva Loureiro; Ricardo Almendra (Urban Science)
Urban green spaces (UGSs) play a vital role in enhancing the quality of life in cities, particularly in rapidly urbanizing regions such as the Metropolitan Region of São Paulo (MRSP). However, significant challenges related to equitable management and access persist, often exacerbated by socio-environmental inequalities. While much of the existing literature on UGS management focuses on developed economies, there is a gap in our understanding of how community engagement influences UGS outcomes in emerging economies, which face unique socio-economic and infrastructural constraints. This study addresses this gap by investigating the impact of community engagement on UGS management in the MRSP, specifically examining how increased participation correlates with improved UGS access and reduced socio-environmental inequality. Utilizing survey data from 33 municipal environmental departments across the MRSP, this research applied correlation tests, generalized linear models, and a non-parametric analysis of variance to evaluate the relationships between community engagement, UGS coverage, and inequality. The findings reveal a moderate positive correlation between community engagement and UGS coverage, alongside a negative correlation with socio-environmental inequality. Increased levels of community participation were associated with greater access to UGSs and a reduction in disparities across socio-economic groups. These results underscore the potential of fostering community involvement in UGS management to promote urban equity and environmental sustainability in emerging economies, particularly through institutional support and transparent information sharing. Future research should focus on longitudinal studies to better understand the long-term effects of sustained community engagement and incorporate qualitative data from community members to provide a more comprehensive analysis of participatory processes. Additionally, expanding the scope of analysis to include informal and private green spaces will offer a more holistic understanding of urban greening dynamics.